2007
DOI: 10.1007/s10911-007-9038-4
|View full text |Cite
|
Sign up to set email alerts
|

The Declining Phase of Lactation: Peripheral or Central, Programmed or Pathological?

Abstract: In most species the functional activity of the mammary gland during lactation follows a biphasic developmental pattern. This pattern starts with a rapid increase in milk output that occurs with secretory activation and continues with a more gradual increase until the point of peak lactation is reached. Following this gain-of-function phase, the ability of the gland to produce milk decreases. This decrease occurs even if the lactation is prolonged by the presence of continued suckling stimulus and complete milk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 81 publications
2
20
0
1
Order By: Relevance
“…Surprisingly, neither the expression of SOCS3 nor the phosphorylation of STAT5 was increased in the mammary glands of PRL-injected dams. Our own previous work on PRL signaling has shown that the recombinant murine PRL used in the present study is capable of inducing mammary STAT5 phosphorylation when administered intravenously to lactating mice (Hadsell et al 2007). In addition, others have demonstrated that exogenous GH and PRL increased the expression of SOCS3 in the mammary tissue of virgin mice (Le Provost et al 2005).…”
Section: Discussionmentioning
confidence: 61%
See 4 more Smart Citations
“…Surprisingly, neither the expression of SOCS3 nor the phosphorylation of STAT5 was increased in the mammary glands of PRL-injected dams. Our own previous work on PRL signaling has shown that the recombinant murine PRL used in the present study is capable of inducing mammary STAT5 phosphorylation when administered intravenously to lactating mice (Hadsell et al 2007). In addition, others have demonstrated that exogenous GH and PRL increased the expression of SOCS3 in the mammary tissue of virgin mice (Le Provost et al 2005).…”
Section: Discussionmentioning
confidence: 61%
“…The second caveat is that mammary gland morphology and wet weight could have been influenced by the timing of tissue sampling relative to the last nursing event between each dam and its pups. While this is meritorious, published data on maternal behavior in rodents, including our own analysis of maternal behavior in mice during prolonged lactation, suggest that because sample collection took place during the day (1000-1200 h), the time period of separation between the dam and its litter would have been no longer than 20 min and was probably much shorter (Sodersten & Eneroth 1984, Hoshino et al 2006, Hadsell et al 2007). These observations strongly support the conclusion that the effects of GH and LR3 were mediated through changes in milk production.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations